PERAN POTENSI STUNTING DALAM MEMPENGARUHI KEBERHASILAN BONUS DEMOGRAFI - Fariq Mahesa Candra Kerti; MirnaNur Alia Abdullah (SABANA: Jurnal Sosiologi, Antropologi, dan Budaya Nusantara, 2024)
Stunting or malnutrition in children is a nutritional disorder that affects growth and development because of insufficient intake of nutrients from consumed food. The impact of stunting on children includes bodily disease such as hampering brain development, bodily disorder, reduced intelligence, and cognitive disorders. This can affect lower levels of education and achievement in children. Low levels of education can influence demographic bonuses, as higher education has the potential to increase the workforce and productivity. The workforce with quality skills plays a crucial role in achieving demographic bonuses, as a workforce with quality skills can enhance living standards and overall economic productivity. The phenomenon of stunting could very well affect the success of the Demographic Bonuses in the future, because looking at the prevalence of stunting in 2007 of 36.8%, children who experienced stunting in that year, will grow up and become one of the generations that contribute to the achievement of the demographic bonus. This article uses a literature study research method from secondary data with a descriptive qualitative approach. This article aims to show the relationship between stunting or malnutrition in children and the achievement of the demographic bonus.